Análise viscoelástica de materiais asfálticos considerando os efeitos da temperatura e do dano - Portela, Enson de Lima (2011)
This work presents an algorithm to modeling the damage and temperature effects on flexible pavements. This formulation considers the material as viscoelastic. It is wellknown not only that asphalt pavements present a mechanical behavior that depends on time, temperature and loading rate but also it can be represented by viscoelastic models. There are some important variables which should be considered for a better performance of the model. Two of then are: Damage and Temperature. This work will study both of then. The increase of the temperature increases the viscous part of the viscoelastic behavior, while the decrease of the temperature increases the elastic part, increasing the material stiffness. The stiffness variation affects the stresses, strains and displacements in asphalt pavements. It is generally accepted in pavement literature that asphalt mixtures can be considered as a thermorheologically simple material and that the Time-Temperature Superposition Principle (TTSP) is valid. Thus, this work presents an algorithm to the viscoelastic analysis of asphalt pavements including the temperature effects. A flexible pavement is analyzed in order to assess the importance of temperature effects on the stresses, strains and displacements in the structural behavior of asphalt pavements. For low stresses the behavior of asphaltic pavements can be accurately modeled using viscoelastic models. However, as the stress level increases distributed micro-cracking arises in the asphalt concrete, leading to permanent deformations. To address these issues, this paper presents a finite element formulation for nonlinear time-dependent analysis of asphalt concrete. The modeling strategy is based on the use of the elastic-viscoelastic correspondence principle and the consideration of micro-cracking through continuum damage mechanics. Considering that the relaxation modulus is given by a Prony series, a very efficient recursive algorithm is obtained where the variables at one time step depend only on the variables of the previous step. The nonlinear equations at both local (constitutive) and global levels are solved by the Newton-Raphson Method. The numerical results using this algorithm will be compared with available solutions